Hasil belajar IPS menggunakan Kolaborasi Model Discovery Learning Berbasis Media Animasi - Darma Putra, I Gede; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2020)
Learning social studies in elementary school should be taught by focusing on students, but the learning process was still focused on the teacher and used lecturing method. Therefore, the aim of this research was to analyze the use of discovery learning models based on animation media. This research was quasi experimental research with non equivalent control group design. The population of this research was all fourth-grade elementary school students which were consisted of 160 students. The samples were taken by random sampling technique. The sample consisted of 31 students in experimental group and 30 students in control group. Data collection was done by using test in the form of multiple-choice test. The data were analyzed by using t-test. The results of data analysis obtained t-count = 3.302 at a significance level of 5% and dk = 59, the value obtained t-table = 2,000 so that t-count = 3.302> t-table = 2,000. So, the use of discovery learning model based on animation media would have an impact on social studies learning outcomes.